Neurological complications in purulent sinusitis - Z. N. Lovpache; I. V. Khulaev; P. B. Kunbutaeva (Лечащий Врач)
Background. The clinical feature of purulent sinusitis, a common but often underdiagnosed disease, has received considerable attention due to its ability to cause severe neurological complications. Although it is often encountered in otolaryngological practice, it can nevertheless be accompanied by severe neurological consequences.Results. A comprehensive review of clinical cases, diagnostic techniques, and therapeutic interventions was performed to provide insight into the pathogenesis, progression, and treatment of these complications. Drawing on the intersection of otolaryngology and neurology, the complexities of diagnosing and treating conditions such as meningitis, intracranial abscesses, and cavernous sinus thrombosis secondary to purulent sinusitis are presented. Case histories for five years were reviewed in a retrospective and prospective manner, and cases of neurological complications were carefully identified and analyzed. Diagnostic strategies for accurately diagnosing and assessing the extent of sinusitis and its neurological involvement are reviewed in detail, with an emphasis on the use of advanced imaging techniques such as high-resolution CT and MRI.Conclusion. Modern research and scientific data on purulent sinusitis provide a complete understanding of the pathology of the disease, diagnostic methods and therapeutic approaches. They emphasize the need for an individualized treatment plan that takes into account the severity of the disease, the patient's overall health, and the potential risks and benefits of various treatment methods. This comprehensive approach, based on the latest scientific evidence, is critical for the effective treatment of purulent sinusitis and its complications.